Critical properties in Dy-doped La0.7−xDyxSr0.3MnO3 (x=0.00, 0.03) manganites. Issue 12 (15th August 2017) - Sfifir, I.; Ezaami, A.; Cheikhrouhou-Koubaa, W.; Cheikhrouhou, A.
Abstract: The critical properties of La0.7−x Dyx Sr0.3 MnO3 (x=0.00 and 0.03) manganites elaborated using sol-gel method have been investigated around the ferromagnetic-paramagnetic (FM-PM) phase transition. The X-ray diffraction characterizations show that the parent compound (x=0.00) crystallized in the rhombohedral structure with R-3C space group without any detectable impurity, while doped sample with (x=0.03) crystallized in the orthorhombic structure with Pnma space group. Various techniques such as modified Arrott plots, Kouvel-Fisher method and critical isotherm analysis were used to determine the values of the Curie temperature TC, as well as the critical exponents β (corresponding to the spontaneous magnetisation), γ (corresponding to the initial susceptibility) and δ (corresponding to the critical magnetisation isotherm). The estimated results are close to those expected by the mean-field model for both samples. The obtained values from critical isotherm M(TC, μ0 H) are close to those determined using the Widom scaling relation, and all data fall on two distinct branches, one for TC and the other for T>TC, indicating that the critical exponents obtained in this work are accurate.